Estimating the geopotential value W0 of the local geoid based on data from local and global normal heights of GPS/leveling points in Vietnam - Hoa, Ha Minh (Geodesy and Cartography, 2013)
Currently, the determination of geopotential value W0 of local geoid that best fits local mean sea level at the Zero Tide Gauge Station is getting important in building the National Geoid-Based Vertical System. Ha Minh Hoa (2007) and Kotsakis et al. (2012) recommended a method, which estimates the geopotential value W0 of local geoid at the Zero Tide Gauge Station based on equations of relation between the local and global normal heights or between the local and global height anomalies at GPS/leveling points regularly located on the whole territory. The objective of this paper is to determine conditions for estimating the geopotential value W0 of local geoid at the Zero Tide Gauge Station accomplished for whole territory of Vietnam.